Using Taxation to Address Noncommunicable Diseases : Lessons from Tonga - World Bank (World Bank, Nuku'alofa, Tonga, 2019)
Tonga has experienced a high burden of noncommunicable diseases (NCDs) in the past two decades. Data indicate the continuing rise of four major NCDs -cardiovascular disease, diabetes, cancer,and respiratory diseases – as the leading causes of premature death and disability. According to latest data, NCDs accounted for four out of five leading causes of mortality in Tonga, and 99.9 percent of Tongan adults aged 25–64 are at moderate to high risk of developing an NCD. The increase in behavioral-related risk factors such as smoking, poor diet (e.g. high in sugar, salt, trans-fat and saturated fat, and low in fruit, vegetables, legumes, fish etc.), harmful alcohol intake, and physical inactivity are acknowledged as the major contributing factors to the rise in NCDs in Tonga. According to its 2012 STEPS Survey, Tonga has one of the highest rates of overweight and obesity (≥25 kg/